Wavelength-dependent study of strong-field Coulomb explosion of hydrogen - Litvinyuk, I. V.; Alnaser, A. S.; Comtois, D.; Ray, D.; Hasan, A. T.; Kieffer, J.-C.; Villeneuve, D. M. (My University, 2008)
We present the first systematic wavelength-dependent study of laser Coulomb explosion of deuterium molecules at various peak intensities and polarizations. We measured the kinetic energy spectra of D+ for laser wavelengths in the range 480–2000 nm. In addition to the well-known enhanced ionization channel present for all wavelengths, we observe a new high-energy band at short wavelengths. This new band exhibits wavelength dependence, with fragment energy decreasing with increasing wavelengths until it merges with the enhanced ionization band for 800 nm and longer. We attribute the emergence of this band to a new pathway that involves resonant three-photon coupling to the first excited electronic state of the molecular ion during the Coulomb explosion process. This pathway should be accounted for in controlling molecular dynamics of hydrogen by intense laser pulses.